Philosophy of Biology in Latin America - Lorenzano, Pablo Julio (2023)
Philosophy of biology is a sub-discipline within philosophy of science, and it became professionalized and institutionalized in regions like the US, Canada, and Europe during the 1970s and 1980s. In Latin America , this process began a decade later, after a long period of early history from the colonial period to the mid-20th century. The professionalization and institutionalization of philosophy of science, including the germination of philosophy of biology, took place between the mid-20th century and the 1980s-1990s. Since then, the field of philosophy of biology grew consistently in Latin America, with contributions of international impact. This article provides an overview of the work done on three topics that are most characteristic of how philosophy of biology has developed in the subcontinent. The themes chosen are the analysis of the concept of race, the analysis of biological theories, and different ways of relating philosophy of biology with history of biology. The main focus is placed on contributions that thinkers living in Latin America have made to philosophy of biology, most of them born in the region. We will also review contributions made by Latin American thinkers working outside the region. This entry has six parts. Sections 1 and 2 provide context for the remainder of the entry. Section 1 gives a brief introduction to philosophy of biology, and Section 2 provides historical background and general characteristics of philosophy of biology in Latin America. Sections 3 through 5 are devoted to the three topics mentioned above: Section 3 to the theme of race, Section 4 to the issue of the nature, structure, and function of biological theories, and Section 5 to the strong connection to history of biology. Section 6 offers final thoughts and considers some future prospects for philosophy of biology in Latin America.